Evaluation of the Development of Islamic Religious Education Learning Materials - Siti Kholizah; Ratna Yanita Kusuma; Hendro Widodo (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The development of Islamic religious education learning materials is crucial in the era of globalization and technological advancement, which indirectly demands renewal and innovation in Islamic religious education learning materials to produce high-quality, relevant, and up-to-date materials that meet the needs of students and can be applied in everyday life. In reality, the development of Islamic religious education learning materials at SDN 0723 Parmainan still faces various challenges, including a lack of integration between general knowledge and Islamic religious education, failing to address global issues, and still focusing primarily on the cognitive domain. In this condition, an in-depth evaluation of the material development is necessary by examining the effectiveness, relevance, and meaningfulness of the material. This study used a qualitative approach with the CIPP evaluation model and was analyzed using the Miles and Huberman analytical framework. The results showed that the evaluation of the development of Islamic religious education materials in terms of content, input, process, and product at SDN 0723 Parmainan was classified as good, but still requires several improvements, including the use of learning technology and providing adequate worship facilities so that the goals of Islamic religious education can be achieved optimally and sustainably.